Chiral analysis of helquats by capillary electrophoresis: resolution of helical N-heteroaromatic dications using randomly sulfated cyclodextrins - Koval, Dušan; Severa, Lukáš; Adriaenssens, Louis; Vávra, Jan; Teplý, Filip; Kašička, Václav (Electrophoresis, 2011)
Enantiomers of helical N-heteroaromatic dications, helquats, were separated by CE. An acidic 22/35 mM sodium/phosphate background electrolyte, pH 2.4, with addition of randomly sulfated α-, β- and γ- cyclodextrins allowed enantioresolution of a series of helquats, which comprised 5, 6 and 7 fused rings participating in the helical backbone. In general, at least one of the chiral selectors was found to provide baseline separation for 22 out of 24 helquats and partial separation for the remaining two. Individually, the sulfated γ-cyclodextrin turned out to separate 79% of the helquats, followed by the β- and α-congeners with 54 and 42% of the resolved compounds, respectively. Migration order of enantiomers was inspected for selected helquats and a relation of molecular size of the analytes to a cavity of the cyclodextrin selectors is discussed.
Keywords: polycyklické sloučeniny; viologeny; Polycyclic Compounds; sírany; Viologens; elektroforéza kapilární; Electrophoresis, Capillary; cyklodextriny; Stereoisomerism; Cyclodextrins; Sulfates; stereoizomerie